ICT sector, digitization and environmental sustainability: A systematic review of the literature from 2000 to 2022 - Lanouar Charfeddine (10705000) (2023)
In line with an intensified call for reducing greenhouse emissions and curbing the effects of climate change, scientists and experts have looked to information communication technology (ICT) and digitization as critical tools for the more efficient use and production of energy. Consequently, research on ICT/digitization and their impact on environmental sustainability has witnessed exponential growth in the last few decades. This study provides a systematic review of the relationship between ICT/digitization and environmental sustainability over the period from January 2000 to April 2022. It aimed to improve our understanding of the different theories and channels governing the ICT/digitization–environmental sustainability nexus, to provide an in-depth analysis and discussion of the trends and main empirical findings of the reviewed articles, and to highlight key avenues for future research. In total, 166 scientific articles examining 297 associations between ICT/digitization and environmental sustainability were selected for this review. The results revealed that most of the studies have used measures based on climate change and air pollution for environmental sustainability, and traditional ICT/digitization measures, e.g., mobile phone subscriptions and internet users. The results also showed that although most studies found evidence for ICT/digitization improving environmental sustainability, evidence for a negative association is concentrated in studies on the ’Group of’ countries. The results also revealed a scarcity of studies investigating nonlinear relationships between ICT/digitization and environmental sustainability. Other Information Published in: Renewable and Sustainable Energy Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rser.2023.113482